Isolated single iron atoms anchored on a N, S-codoped hierarchically ordered porous carbon framework for highly efficient oxygen reduction. Issue 16 (15th April 2021) - Liu, Xinghuan; Zhai, Xingwu; Sheng, Wenbo; Tu, Juan; Zhao, Zeyu; Shi, Yulin; Xu, Caixia; Ge, Guixian; Jia, Xin
Abstract : An in situ gas-foaming strategy was presented to prepare atomic Fe anchored on N, S-codoped hierarchically ordered porous carbon (HOPC) framework. The HOPC and FeN4 S2 catalytic centers make it exhibit superb ORR and Zn–air battery properties. Abstract : Atomically dispersed metal catalysts are promising candidates for the oxygen reduction reaction (ORR) and for achieving efficient energy conversion. However, rational design of single atom catalysts (SACs) with high-efficiency ORR catalytic activity and superior stability is still crucial yet challenging. Herein, an in situ gas-foaming methodology is presented for constructing single Fe atoms dispersed on a N, S-codoped (FeSA /NSC) hierarchically ordered porous carbon (HOPC) framework via one-step pyrolysis of dopamine (DA)/Fe 3+ complexes and thiourea in SBA-15 channels. HOPC structures (facilitating active site access and mass transfer) and optimized FeN4 S2 catalytic centers make FeSA /NSC exhibit high ORR activity with a half-wave potential ( E 1/2 ) of 0.91 V, fuel selectivity and long-term stability (3 mV negative shift after 5000 potential cycles) in 0.1 M KOH. It even shows comparable ORR catalytic activity ( E 1/2 = 0.78 V) to the Pt/C catalyst in acidic electrolytes. As the air electrode in zinc–air batteries, FeSA /NSC demonstrates superior power density, long-term discharge stability and specific capacity to the commercial Pt/C catalyst. Thus, FeSA /NSC is a promising non-platinum-group metal ORR catalyst for the ORR and application in zinc–air batteries.